Policy Formulation, Analytical Frameworks, and Program Design. (Policy Papers; Policy Paper, 2004)
The first part of this paper lays out the process of program design and briefly describes some of the analytical tools--including the financial programming framework, the balance sheet approach, and the debt sustainability template--employed by Fund country teams in advising national authorities on policy formulation. The second part of paper seeks to assess how well this process works in practice.